Synthesis of 3D Cu(OH)2 nanoflower thin film by room temperature chemical method for high performing positive electrode in supercapacitor. (2021) - Salokhe, Balaji; Gonugade, Madhuri; Patil, S.B.; Kim, J.H.; Gurav, K.V.
Graphical abstract: Abstract: Herein, we report synthesis of three dimensional (3D) copper hydroxide [Cu(OH)2 ] nanoflower thin film by room temperature successive ionic layer and adsorption reaction (SILAR) method. The synthesized film is characterized for its structural, chemical, surface morphological properties by means of X-ray diffraction (XRD), Fourier transform infrared (FT-IR) and field emission scanning electron microscopy (FE-SEM), respectively. The XRD analysis shows the deposited film is amorphous in nature, formation of copper compound with hydroxide phase is confirmed by FT-IR study. The FE-SEM analysis reveals the nanoflower morphology of the deposited material. Moreover, FE-SEM micrograph shows the entire surface of the substrate is uniformly covered by Cu(OH)2 nanoflowers. When employed as the positive electrode in supercapacitor device, the Cu(OH)2 nanoflower thin film exhibits highest specific capacitance which exceeds 283 Fg −1 at 10 mVs −1 in 1 M KOH electrolyte, which demonstrates that the hydrous 3D Cu(OH)2 nanoflowers with porous morphology can effectively be used in supercapacitor application.